The competition in the labor market between immigrants and natives - Martínez Veiga, Ubaldo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Although it is frequently thought that there is no competition in the labour market between immigrants and the native population, possible areas of competition are here analysed. The interpretation of the dual labour market is criticized and it is argued that, within capitalism, the attempt to prevent some groups from competing, freezes them for good in a subordinate position.